ChemInform Abstract: Disorder‐Controlled Electrical Properties in the Ho2Sb1‐xBixO2 Systems. Issue 26 (6th June 2013) - Wang, Peng L.; Kolodiazhnyi, Taras; Yao, Jinlei; Mozharivskyj, Yurij
Abstract Samples of the title phases are prepared over the whole composition range (x = 0—1.0) from mixtures of Ho, Sb, Bi, and Ho2O3 (pressed pellets, evacuated silica tubes, 800 °C, 48 h and 1000 °C, 20 h).